Long-term effects of biological sprout control of unwanted hardwoods on conifer sites - Hamberg, Leena; Laine, Tiina; Hantula, Jarkko; Saksa, Timo (My University, 2021)
Long-term investigations revealing the effects of a decay fungus, Chondrostereum purpureum (Pers. Ex Fr.) Pouzar on competition between deciduous and conifer tree species in young forests are missing. Therefore, the effects of three different sprout control treatments were tested in young Norway spruce (Picea abies (L.) H. Karst.) and Scots pine (Pinus sylvestris L.) stands by evaluating sprouting ability of deciduous tree stumps, and competition level around cultivated conifers five years after the treatments. Sprouting control was performed (i) by cutting only (control), and ii) by applying low-concentration (dilution 1:400) or iii) high-concentration (dilution 1:100) C. purpureum preparates (mycelial solutions) on stumps immediately after cutting. Deciduous saplings were cut, and fungal inoculum was applied by spreading it onto freshly cut stump surfaces. Following high-concentration fungal treatment, the number of young deciduous trees cut in the treatment was by 25% lower compared to control; moreover, the number of sprouts per stump was also significantly negatively affected by the fungal treatment. As a result, the number of cases when competing deciduous trees occurred within a 1 m sample plot around the investigated conifers was 40% lower following high-concentration fungal treatment than in the control, resulting in better height and diameter development of conifers. Thus, additional sprout control is not necessarily needed after the high-concentration fungal treatment.
Keywords: Decay fungus; Chondrostereum purpureum; Competition; Stump treatment; Vegetation management